Whole issue - Language Value (Universitat Jaume I. Department of English Studies, 2020)
Table of Contents From the editors Ruth Breeze Articles  New research genres and English prosody: an exploratory analysis of academic English intonation in Video Methods Articles in experimental biology Ignacio Guillén Galve Miguel A. Vela Tafalla The impact of peer assessment on the attainment level of oral presentations skills Bojan Prosenjak Iva Lučev EMI teacher training with a multimodal and interactive approach: A new horizon for LSP specialists Teresa Morell English, Spanish o los dos? Teaching professional writing on the U.S.-Mexico border Theresa Donovan Teresa Quezada Isabel Baca Maps of student genres in engineering: a didactic model for teaching academic and professional Spanish language Enrique Sologuren Insúa Book and Multimedia Reviews  Ken Hyland and Lillian L. C. Wong. Specialised English: New Directions in ESP and EAP Research and Practice Gang Yao